Análise integrativa do comportamento e do desempenho de bovinos em terminação com inclusão de grão de girassol na dieta - Maidana, Fabiana Moro (2021)
World agricultural production guarantees a diversity of products to fill animal feed, however, some food sources are still little known in zootechnical nutrition. Sunflower grain is, due to its high content of ether extract, not often used in ruminants’ diet, however, it can represent an alternative energy source for inclusion in the diet of finishing cattle. The aim of this study was to evaluate the ingestive behavior and performance of cattle finished in feedlot including increasing levels of sunflower grain in the diet. Thirty-six non-castrated male bovines from the cross between Charolais and Nellore breeds were used, with an average age of 20 months and an initial average weight of 311.78 kg (± 29.99), distributed in four food treatments. The treatments were the inclusion of: 0, 50, 100 or 150 grams of sunflower grain per kilogram of dry matter in the diet, containing contents of 4.12; 6.53; 8.91 and 11.28% of ether extract in the diets, respectively. The experimental diets showed a roughage: concentrate ratio of 48:52 and 13.6% of crude protein. The experimental design used was completely randomized with four treatments and nine replications. The slaughter of the animals occurred as they reached an average live weight of 440 kg within each treatment, reaching the periods of 80, 80, 101 and 138 days of confinement, in the treatments including 0, 50, 100 and 150 g/kg of sunflower grain dry matter (DM), respectively. The highest intake of total dry matter, relationship between dry matter and live weight (LW), crude protein, neutral detergent fiber, total digestible nutrients and digestible energy occurred in treatments without inclusion and 50 g/kg DM of sunflower grain included, while the lowest intake was in treatments with 100 and 150 g/kg DM of sunflower grain. The highest intake of ether extract was observed in the treatments including 100 and 150 g/kg DM of sunflower grain and the lowest in the treatment without the addition of this grain in the diet. The behavioral responses demonstrate that the chews per cud and the chewing time per cud were higher in the treatment with the addition of 150 g/kg DM of sunflower grain and lower in the treatment without addition of this ingredient. Still for these treatments, there is a difference for the performance measurements, in which the daily gain and feed conversion were better in the treatment with 0 (1.77 kg/day and 5.78 kg DM/kg LW, respectively) and worse in the treatment with 150 g/kg DM of sunflower grain (1.00 kg/day and 8.07 kg DM/kg LW, respectively). The results support that the sunflower grain changes the dietary intake and regulatory mechanisms of ingestion, influencing dry matter and nutrients intake, so consequently, alters the performance of feedlot cattle.